Associations between residential greenness and asthma and allergic rhinitis in children: A systematic review and meta-analysis. (July 2023) - Liu, Wei; Liu, Kailun; Cai, Jiao; Ma, Shuang; Yang, Minghan; Yang, Quan; Yuan, Yanping
Highlights: 23 studies for effects of greenness on childhood asthma and rhinitis were reviewed. Higher NDVI close to residence within 100m may decrease risk of childhood asthma. Higher residential NDVI within 500m may increase odd of childhood allergic rhinitis. Abstract: Several studies suggested that residential greenness was associated with childhood asthma and allergic rhinitis. However, associations were inconsistent and it's still limited for the meta-analyses of associations in these studies. Here we aimed to provide state-of-the-art evidence for associations of residential greenness with asthma and allergic rhinitis in childhood. We systematically reviewed the relevant studies from five databases since database inception to December 2020 and meta-analyzed associations of residential greenness with childhood respiratory diseases from 23 original articles. Our meta-analyses indicated that childhood asthma was negatively associated with normalized difference vegetation index (NDVI) within 100m of residence (pooled OR, 95%CI: 0.88, 0.83-0.93), but had no significant association with greenness within 500m of residence (1.10, 0.99-1.23). NDVI within the 500m of residence had significant and positive associations with allergic rhinitis among 6-8-years-old children (1.21, 1.07-1.38), but was not significantly associated with allergic rhinitis among 9-12-years-old children (1.02, 0.93-1.12). Similar associations were found in sensitivity analyses. Our findings indicate that residential greenness could have significant effects on preschoolers' asthma and allergic rhinitis. However, effect directions on asthma and allergic rhinitis are inconsistent among different study populations and among studies using different indicators of residential greenness.